Historische und aktuelle Perspektiven im Dienstleistungshandel - Holger Breinlich (Wirtschaftsdienst, 2018)
Der internationale Dienstleistungshandel spielt eine immer bedeutendere Rolle im Welthandel. Hierbei muss im Gegensatz zu Zollschranken im Warenhandel auf die nicht-tarifären Handelshemmnisse geschaut werden, die oft nur schwer quantifizierbar sind. Der Autor diskutiert Handelsbarrieren, den Brexit sowie die damit verbundenen Bedrohungen für den Dienstleistungshandel in Europa. – – Trade in services has expanded rapidly over the past several decades and now represents around a quarter of world trade, or approximately USD 5 trillion. This article gives an overview of historical and recent developments in services trade. It includes a discussion of the different definitions of services trade and the problems of accurate statistical measurement. It also presents selected recent research findings on the characteristics of services traders, firm level trade patterns, measurement of trade barriers, and the effects of trade liberalisation and regional integration on services trade, with a particular focus on the United Kingdom's exit from the European Union (Brexit).
Keywords: F13; F14; F15; 330